(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2022)
Studies of peace and social justice-focused education have long explored the role of pedagogy in enabling individual transformation and moving towards social change (Bajaj et al, 2017; Finley, 2004). Indeed, the fields of peace and human rights education have increasingly emphasized critical, feminist, and transformative pedagogies as fundamental for developing a critical consciousness and motivation to act among young people (Bajaj & Hantzopoulos, 2016, 2021; Jenkins, 2016; Zembylas, 2013)